A Study on the Correlation Between Quality of Life and Unhealthy Emotion Among Patients With Endometriosis - He, Guimei; Chen, Jiebing; Peng, Zhangqing; Feng, Kai; Luo, Chunqi; Zeng, Xun (Frontiers in Psychology, 2022)
Objective To investigate the influence of quality of life (QOL) on unhealthy emotions as well as relevant factors among patients with endometriosis for supporting relevant clinical care. Methods A convenience sampling method was used to administer questionnaires to 139 patients with endometriosis, using the Hamilton Anxiety Inventory (HAMA), the Depression Anxiety Scale (SDS), and the SF-12 Health Survey Short Form, and the results were analyzed. The SPSS20.0 software was used for statistical analysis on relevant data. If P < 0.05, there was statistical significance. Results Twelve-Item Short Form (SF-12) for health survey covered two comprehensive indexes, i.e., physical component summary (PCS) and mental component summary (MCS) scores. MCS score was the main factor influencing anxiety and depression in patients with endometriosis; the higher the MCS score, the lower the anxiety and depression degrees in patients with endometriosis (OR = 0.912, 95% CI: 0.877–0.949; OR = 0.899, 95% CI: 0.866–0.933). PCS score was a factor influencing anxiety degree; the higher the PCS score, the lower the anxiety degree (OR = 0.936, 95% CI: 0.891–0.983). Conclusion The QOL of patients with endometriosis is negatively correlated with anxiety and depression. Therefore, improvement in QOL may help relevant patients to relieve their unhealthy emotions.